Extensive HLA class I allele promiscuity among viral CTL epitopes - Frahm, Nicole; Yusim, Karina; Suscovich, Todd J.; Adams, Sharon; Sidney, John; Hraber, Peter; Hewitt, Hannah S.; Linde, Caitlyn H.; Kavanagh, Daniel G.; Woodberry, Tonia; Henry, Leah M.; Faircloth, Kellie; et al. (European Journal of Immunology, 2007)
Promiscuous binding of T helper epitopes to MHC class II molecules has been well established, but few examples of promiscuous class I-restricted epitopes exist. To address the extent of promiscuity of HLA class I peptides, responses to 242 well-defined viral epitopes were tested in 100 subjects regardless of the individuals' HLA type. Surprisingly, half of all detected responses were seen in the absence of the originally reported restricting HLA class I allele, and only 3% of epitopes were recognized exclusively in the presence of their original allele. Functional assays confirmed the frequent recognition of HLA class I-restricted T cell epitopes on several alternative alleles across HLA class I supertypes and encoded on different class I loci. These data have significant implications for the understanding of MHC class I-restricted antigen presentation and vaccine development.